ANALISIS KESALAHAN SISWA MENYELESAIKAN SOAL CERITA PADA MATA PELAJARAN MATEMATIKA MATERI JARAK DAN KECEPATAN DI KELAS V SDN 3 SENENAN - Andriani, Sefti Mellenia; Zumarnis, Nurul Aprilia; Wulandari , Hanifah (Unika Santo Thomas Medan, 2022)
The research that was carried out had the aim of finding out what mistakes made students difficult in learning mathematics, especially in the material of measuring distance and speed, as well as what difficulties students felt in working on word problems regarding measuring distance and speed related to daily life. -day. The research was conducted in class V which consisted of 19 students. The way to collect the data yourself is that the researcher gives 4 story questions to students, a total of 19 students, but the data collection that can be taken by researchers is 5 students. This type of research is a qualitative case study. Data collection techniques used are interviews, documentation and observation. Data analysis techniques using descriptive. The results of the analysis of the data obtained in the first picture are the results of the student's completion when they are wrong in writing symbols, the second is the result of the student's solution being wrong in determining the method used, the third is the result of the completion of students who do not understand what is known and asked, and the fourth is the result of the completion of the stage solve story problems. The results of this study are expected that students will be able to overcome factors and students' difficulties in solving word problems in measuring distances and students can understand the questions. The offering solution is to identify student difficulty problems, provide individual guidance and provide motivation and rewards to students.